Workshop Perancangan Kurikulum Pendidikan Kesehatan Mental Bagi Calon Guru di Indonesia - Kadriyan, Hamsu; Gunawan, Gunawan; Puspitasari, Dian; Warnaini, Cut; Suranti, Ni Made Yeni; Astini, Baik Nilawati (Indonesian Journal of Education and Community Services, 2024)
Mental health is a crucial aspect of education, particularly for prospective teachers who will play a significant role in shaping students' character and well-being. This community service activity aimed to enhance the capacity of prospective teachers in understanding and managing mental health through a Curriculum Design Workshop on Mental Health. The workshop involved 25 participants, comprising mental health researchers, curriculum experts, experts in mental health and clinical psychology, experts in guidance and counseling and psychology, as well as lecturers supervising mental health-related educational courses. The outcomes of this workshop included the development of a survey instrument for assessing the mental health profiles of prospective teachers, along with documents and other instruments to support the design of a comprehensive and applicable mental health curriculum. This activity is expected to contribute to the improvement of the quality of education and mental well-being in the school environment.